Elucidating the preventive and therapeutic effects of cardiac telocytes paracrine microRNAs on ischemic heart disease - Jiang, Hugang; Tang, Yan; Liu, Ai; Ren, Chunzhen; Lin, Wenyan; Liu, Kai; Zhao, Xinke; Li, Yingdong (Frontiers in Cardiovascular Medicine, 2025)
Telocytes (TCs), a newly identified type of mesenchymal cell since 2010, possess substantial potential in maintaining tissue homeostasis, orchestrating organ development, and facilitating tissue regeneration. Their distribution in blood, the adventitia of blood vessels, and the intima implies a close association with vascular function. Ischemic heart disease (IHD), a significant challenge in cardiovascular disease, is characterized by the occlusion of major vessels, obstruction of collateral circulation, and disruption of the capillary network—pathological features closely linked to endothelial cell damage. Myocardial tissue is rich in cardiac telocytes (cTCs), which, following myocardial injury, can secrete numerous miRNAs that promote angiogenesis, including miR-let-7e, miR-10a, and miR-126-3p. This indicates that cTCs may have therapeutic potential for IHD. The primary mechanism by which cTCs-derived exosomes exert paracrine effects is through reducing endothelial cell injury, suggesting that enhancing the production of cTCs could offer a novel therapeutic approach for treating IHD.